Beyond Pollination: Honey Bees (Apis mellifera) as Zootherapy Keystone Species - Easton-Calabria, August; Demary, Kristian C.; Oner, Nola J. (Frontiers in Ecology and Evolution, 2019)
The ‘extended phenotype’ expands on the phenotype concept to encompass all effects of a gene, including those that a gene may have on an organism’s surrounding environment. Honey bees (Apis mellifera) can be considered a keystone species that exerts a strong impact on its community through their extended phenotypes that relate to disease resistance. Honey bee extended phenotypes (i.e. honey, propolis, venom, beeswax, bee bread and royal jelly) confer pathogen/pest resistance. Each of these extended phenotypes have been shown to exhibit antipathogenic properties and to act as a colony-level defense mechanism against disease. The phenomenon of a collective immune defense in social insects, termed social immunity, has evolved for defense against pathogens which spread easily in highly dense eusocial systems, such as that of honey bees. Additionally, humans can use the extended phenotypes from honey bees for pathogen resistance. The implication of these phenomena is that honey bees, through their genes, can manipulate their community structure both within and without the hive.